Integrative Holistic Garden at Early Childhood Education to Reduce Children Stunting - Banoet, Jendriadi; Sutarto, Joko; Handayani, Sri Sularti Dewanti (Universitas Negeri Semarang, 2020)
This study aims to analyze and to describe the planning, organizing, implementing and supervising of the integrative holistic early childhood education garden program at Marsudirini Fioretti Kindergarten. This research used qualitative method and study case approach. The data resources were obtained from the mentors who were the headmaster of the kindergarten, teachers, and parents. The techniques of data collections were observation, interview and documentation. Integrative holistic garden at early childhood education is a program of growth and development services combined to meet the nutritional intake which is in accordance with the stage of age development of the child as an effort to support the independency of institutions and learning laboratories for children. The results of this study are that the planning for the integrative holistic garden at early childhood education is quite good with the preparation of the plantation program, funding and development of sub-activity plans, but organizing part is less effective in the distribution of tasks and setting schedules, for that, the implementation of direction, motivation and coordination needs to be done as well as the preparation for facilities. So that, the integrative holistic garden program could be more effective. The garden supervision from Marsudrini Kindergarten and related government regarding the program has been carried out but there is still a lack of follow-up in the form of guidance that is necessary in the management of garden products for the fulfillment of children's nutrition, supporting the independency of institutions and learning laboratories for children.